2019
DOI: 10.1055/a-1010-6887
|View full text |Cite
|
Sign up to set email alerts
|

Psychometrische Evaluation der deutschen Version des Semistrukturierten Interviews zur Erfassung der DSM-5 Persönlichkeitsfunktionen (STiP-5.1)

Abstract: Zusammenfassung Theoretischer Hintergrund Das alternative Modell für Persönlichkeitsstörungen des DSM-5 führt erstmals ein evidenzbasiertes, dimensionales Konzept für die Diagnostik von Störungen der Persönlichkeit ein. Kriterium A, operationalisiert mit der Level of Personality Functioning Scale, differenziert das Ausmaß von Beeinträchtigungen im Funktionsniveau der Persönlichkeit. Mit dem Semi-Structured Interview for Personality Functioning DSM-5 (STiP-5.1) liegt bereits ein valides, reliables un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 26 publications
2
30
1
1
Order By: Relevance
“…The findings regarding reliability are in line with the original study of the STiP‐5.1 with high internal consistency—Cronbach's α = 0.97 (Hutsebaut et al, 2017). Previous studies reported satisfactory interrater reliability (ICC) measuring the degree of agreement among interviewers (ranging in total from 0.58 to 0.92; Hutsebaut et al, 2017; Zettl et al, 2019). Due to organizational reasons and a 1:1 setting, with no audio or visual recordings, it was not possible to include this measure into our study.…”
Section: Discussionmentioning
confidence: 99%
“…The findings regarding reliability are in line with the original study of the STiP‐5.1 with high internal consistency—Cronbach's α = 0.97 (Hutsebaut et al, 2017). Previous studies reported satisfactory interrater reliability (ICC) measuring the degree of agreement among interviewers (ranging in total from 0.58 to 0.92; Hutsebaut et al, 2017; Zettl et al, 2019). Due to organizational reasons and a 1:1 setting, with no audio or visual recordings, it was not possible to include this measure into our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is significantly associated with overall symptom severity and the diagnosis of a personality disorder (Ehrenthal et al, 2012), but also other measures of personality difficulties (Zimmermann et al, 2014;König et al, 2016). Even more importantly, it correlates with OPD personality functioning expert ratings (r = 0.62; Dinger et al, 2019), and its 12-item short version (Ehrenthal et al, 2015) also with DSM-5 LPFS interview ratings (r = 0.78; Zettl et al, 2019). Initial adaptation and validation of the instrument for Chile (De la Parra et al, 2018) shows from an acceptable to high internal consistency scores (α = 0.71-0.93 for subscales).…”
Section: Personality Functioning (Opd-sq)mentioning
confidence: 97%
“…Additionally, two structured interview schedules have been designed to specifically address the 12 facets of the LPFS: the Structured Clinical Interview for DSM-5 Alternative Model for Personality Disorders module I [SCID-5-AMPD-I; (12)] and the Semi-Structured Interview for DSM-5 Personality functioning [STiP-5.1; (13,14)]. Both interview schedules showed promising results regarding reliability and validity of assessments of personality functioning (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%